Self-assembly directed template photopolymerization of perylenebisimide-poly (4-vinylpyridine): nano organization - Shinde, Shekhar; Asha, S. K. (Polymer, 2015)
A perylene bisimide derivative (PDP-UPBIAcry) having hydroxyl moieties at one termini and polymerizable acrylic units at the other termini was supramolecularly complexed with the pyridine units of Poly (4-vinyl pyridine) (P4VP), followed by photoinduced polymerization of the acrylic units to obtain lamellar organization in the <10 nm range. H-1 NMR studies including variable temperature (20 degrees C-70 degrees C) measurements were undertaken in DMSO-d(6) (anhydrous, extra dry) to understand the interaction between PDP-UPBIAcry and P4VP. The aromatic perylene protons of PDP-UPBIAcry registered an upfield chemical shift while the pyridine protons of P4VP exhibited small downfield shift in their 1:1 supramolecular complex. The hydrogen bonding interaction between pyridyl nitrogen and phenolic OH group was also traced in non-polar media like CDCl3 in model complexes of 4-vinyl pyridine (4VP) with PDP-UPBIAcry. Wide angle X-ray diffraction (WXRD) technique was used to study the bulk structure. Transmission electron microscopy (TEM) imaging revealed highly ordered layered assembly formed upon complexation. Observation from DFT energy minimization studies were correlated with X-ray diffraction data of the supramolecular complex [P4VP (PDP-UPBIAcry)](1.0) to understand the nature of packing of PDP-UPBIAcry that lead to the formation of highly ordered lamellar stacks alternating with P4VP. The higher ordering in the supramolecular polymer complex was also confirmed by the quenching of fluorescence and reduced fluorescence life times of thin solid films of the [P4VP Poly(PDP-UPBIAcry)](1.0) sample. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: hydrogen bonding; P4VP; Perylenebisimide